EFEKTIVITAS PEMBELAJARAN AUDITORY, INTELLECTUALLY, REPETITION (AIR) TERHADAP HASIL BELAJAR SISWA DI SD MUHAMMADIYAH KEMIRI - Amelia, Ida; Ihtiari, Dhiya Ayu Tsamrotul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research is motivated by the low learning outcomes of Pancasila Education among fourth grade students of SD Muhammadiyah Kemiri as shown by the data that 35% of students scored below the KKM. This research aims to identify the effectiveness of Auditory, Intellectually, Repetition (AIR) learning model compared to conventional model in improving students' learning outcomes. This research used a pseudo-experimental design with post-test only control design involving two groups of students. The population in this study were all fourth grade students of SD Muhammadiyah Kemiri. The research sample consisted of 20 students selected using simple random sampling technique. The instrument used was a learning outcome test. Data analysis used nonparametric statistics Mann-Whitney U. The results of hypothesis testing showed significant results with a p-value = 0.005 <0.05. This indicates that the learning outcomes of students given the AIR learning model are better than those of students given the conventional learning method. The results of this study indicate that the AIR method, which emphasizes learning through auditory, intellectual, and repetition, is effective in improving students' understanding and retention. This finding supports constructivist learning theory and reinforces the importance of repetition as a strategy in learning. The implication of this study is the need for integration of AIR model in the learning curriculum to overcome the limitations of conventional methods and improve students' overall learning outcomes.